-3(-2*x+4)-(x-6)=y

Simple and best practice solution for -3(-2*x+4)-(x-6)=y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-2*x+4)-(x-6)=y equation:


Simplifying
-3(-2x + 4) + -1(x + -6) = y

Reorder the terms:
-3(4 + -2x) + -1(x + -6) = y
(4 * -3 + -2x * -3) + -1(x + -6) = y
(-12 + 6x) + -1(x + -6) = y

Reorder the terms:
-12 + 6x + -1(-6 + x) = y
-12 + 6x + (-6 * -1 + x * -1) = y
-12 + 6x + (6 + -1x) = y

Reorder the terms:
-12 + 6 + 6x + -1x = y

Combine like terms: -12 + 6 = -6
-6 + 6x + -1x = y

Combine like terms: 6x + -1x = 5x
-6 + 5x = y

Solving
-6 + 5x = y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 5x = 6 + y

Combine like terms: -6 + 6 = 0
0 + 5x = 6 + y
5x = 6 + y

Divide each side by '5'.
x = 1.2 + 0.2y

Simplifying
x = 1.2 + 0.2y

See similar equations:

| f(m)=20-0.25m | | 69-5x=4x+18 | | 3y-10=5x+22 | | x^2=-13 | | -17x-20=-14x+70 | | -7/3(y-12)-1/6y=0 | | 3/4x-3/2=6 | | -7/3(y-12)-1/6y | | 4x+9=3x+17 | | 3x+7=2x+15 | | 5x^3/2-35=100 | | -177=9*n | | 11x-3=3x+21 | | 9x+18=27 | | 5x-35=100 | | 6x-5=31-2x | | 24-3x=56+2x | | 3x-4(7x+3)=5x+7(9x-10) | | 5.59+55.9=111.8 | | -17-(-40)=x/2 | | X=2(-2)+6 | | X*13-110=x*6-12 | | 5(5c-1)-3=23c+2 | | 3x/2+5=16x-11 | | 8w=4.2 | | 2/5n=24 | | 5-8x=92-29x | | -2k+3k-9+5k=0 | | 3/4*29/6 | | 6-10x=43x+17 | | 3(u+4)=(5+u)5 | | -4(5y-6)+2(2y+9)=0 |

Equations solver categories